The Sundanese Pop Music of Nano Suratno: Between Tradition and Adaptation - Gunara, Sandie (TAWARIKH, 2014)
ABSTRACT: Talking about Sundanese pop music principally means talking about the concept of Sundanese music itself, which is, indeed, packaged differently. Historically, commercial music (pop music) in developing countries, such as Indonesia, did not destruct the originality of âsoundsâ in its local pop music; rather, it enriched the local music. The imported pop culture is a resource, a source of information on new sounds, instruments, and ideas, which can be exploited by local artists to create âa different taste of musicâ based on their capabilities. Popular music today is made for commercial purposes, even a commodity; however, sometimes it does not lack quality. Consequently, it is very difficult to make something original in popular music, for if originality is emphasized, people will sense that there is something uncommon in the song. On the other hand, if it lacks originality, its quality will be lowered. The aim of this paper is to discuss on Sundanese pop music. The issues covered: the existence of pop music, the existence of recording industries and Sundanese pop music, and local identity and Sundanese pop music industries, more specifically concerning the case of Nano Suratno that known as Nano S. Based on the conducted study, two hypotheses were put forward. Firstly, the Sundanese pop music of Nano Suratno is based on creative considerations; where in quality, uniqueness, and adaptation are maintained. Secondly, the Sundanese pop music of Nano Suratno is a spirit in counter balancing the national pop music industries. KEY WORDS: Popular music, Sundanese pop music, figure of Nano Suratno, tradition, structuration, adaptation, and local identity.Â  Â About the Author: Sandie Gunara is a faculty member of Music Education Department, Faculty of Language and Art Education UPI (Indonesia University of Education), Jalan Dr. Setiabudhi No.229 Bandung 40154, West Java, Indonesia. He is currently taking his doctoral studies in the Department of Cultural Studies UNPAD (Padjadjaran University) Bandung, West Java, Indonesia. He can be reached by email at: sandiegunara@yahoo.comHow to cite this article? Gunara, Sandie. (2014). âThe Sundanese Pop Music of Nano Suratno: Between Tradition and Adaptationâ in TAWARIKH: International Journal for Historical Studies, Vol.6(1) October, pp.35-42. Bandung, Indonesia: Minda Masagi Press and UNHAS Makassar, ISSN 2085-0980. Chronicle of the article: Accepted (August 4, 2014); Revised (September 17, 2014); and Published (October 28, 2014). Â